2016
DOI: 10.1002/etc.3571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the herbicide surfactant MON 0818 on oviposition and viability of eggs of the ramshorn snail (Planorbella pilsbryi)

Abstract: The surfactant mixture MON 0818 is an adjuvant in various commercial formulations of the herbicide glyphosate. Initial studies have shown that MON 0818 is more toxic to aquatic animals than the active ingredient. However, few studies have examined the effect of exposure to MON 0818 on species of mollusks, and no studies have examined the effect on gastropods. The present study investigated the effect of acute exposure (96 h) of MON 0818 to the eggs, juveniles, and adults of the file ramshorn snail (Planorbella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…In the Parental Recovery, snails in the highest treatment (75.0 lg/L Cu) were the first to begin laying egg masses, possibly indicating an overcompensation mechanism after the week-long inhibition of mobility and reproduction. The same species (P. pilsbryi) demonstrated recovery with overcompensation in reproduction when exposed to sublethal concentrations of the surfactant MON 0818, resulting in significantly higher egg production in treatment groups exposed to the highest concentrations compared with those that were not exposed (Prosser et al 2017). This response is similar to what was observed in the current study with exposure to sublethal concentrations of Cu resulting in faster oviposition (Fig.…”
Section: Reproductive Timingsupporting
confidence: 85%
“…In the Parental Recovery, snails in the highest treatment (75.0 lg/L Cu) were the first to begin laying egg masses, possibly indicating an overcompensation mechanism after the week-long inhibition of mobility and reproduction. The same species (P. pilsbryi) demonstrated recovery with overcompensation in reproduction when exposed to sublethal concentrations of the surfactant MON 0818, resulting in significantly higher egg production in treatment groups exposed to the highest concentrations compared with those that were not exposed (Prosser et al 2017). This response is similar to what was observed in the current study with exposure to sublethal concentrations of Cu resulting in faster oviposition (Fig.…”
Section: Reproductive Timingsupporting
confidence: 85%
“…Among a number of surfactants used in the formulation of PPPs (Table 1), POEA appears to be associated with highest toxicity concerns, particularly in of formulated glyphosate-based PPPs (Romano et al, 2010;Mesnage et al, 2013a;Székács et al, 2014;Farkas et al, 2018). Considering this unfavorable toxicity profile, particularly as related to aquatic toxicity (Prosser et al, 2017;Rodriguez-Gil et al, 2017a,b), cytotoxicity and also the assessment by EFSA (European Food Safety Authority, 2015c), the EC has recommended EU MSs in September, 2016 to exclude POEA as a co-formulant from the use in PPPs containing glyphosate (European Commission, 2016a,b). As a result, a number of glyphosate-based herbicides containing POEA as a formulant have been banned for use in Hungary ( Table 2) (National Food Chain Safety Office, 2016) and in other EU MSs.…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 99%
“… 32 for earthworms, springtails, and predatory soil mites, and also in the present study for springtails. The differences between observations with the active substance and the formulation tested in our study must therefore consider the adjuvants used in the formulation to enhance stability and penetration of the active compounds into plant cells 33 . Adjuvants are declared as inert diluents, not being directly responsible for the intended pesticide activity 24 , although effects on other non-target organisms are known.…”
Section: Discussionmentioning
confidence: 85%
“…Ethoxylated adjuvants are substances with a surfactant action, having alkyl chains and/or ethoxy groups in the ethoxylated chains, which can penetrate cell membranes disrupting their structure and functions 34 . Contrary to what is expected from a pesticide adjuvant, POEA has been reported in the last few years to present even higher toxicity to non-plant organisms than glyphosate alone 33 , 35 . A statement released by EFSA 36 on this subject concluded that “compared to glyphosate, a higher toxicity of the POE-tallowamine was observed on all endpoints investigated”.…”
Section: Discussionmentioning
confidence: 97%